Products of plant origin – benefits and the potential risk for the consumer - Karasiewicz, Monika; Bogacz, Anna; Krzysztoszek, Jana; Pędziwiatr, Daniel; Czerny, Bogusław (Journal of Medical Science, 2017)
Phytochemical compounds are widely used in traditional medicine in the treatment of many ailments. In recent years, an increasing interest is observed in the use of new natural bioactive substances and whole standardized extracts in the prevention and therapy of diseases. Some of these are the components of the diet, diet supplements or at higher doses are used as herbal medicines. Many phytochemicals have documented a beneficial effect on health, but they must be used properly. Therefore, it is important to inform about differentiating between herbal medicine and dietary supplement. Further, the possibility of interactions with synthetic drugs and the mechanisms of these effects is necessary to describe for the safety of phytotherapy. The goal of our paper is to show high prophylactic and medicinal potential of natural active compounds of plant origin. We also want to draw attention to the safety of their use by the consumer. Therefore, we present some studies on the benefical properties of natural active compounds, mainly in the prevention and treatment of cancers and neurodegenerative diseases. The results of the described studies are extensively discussed and their suitability for further testing in vivo and in clinical trials is examined. At the same time we show selected interaction of common medicinal plants or their raw materials with synthetic drugs.